How to win friends and influence people in the digital age - Cole, Brent (Simon & Schuster, 2011)
An up-to-the-minute adaptation of Dale Carnegie's timeless, commonsense approach to communicating. In today's world, where more and more of our communication takes place across wires and screens, Carnegie's lessons have not only lasted but become all the more critical.